K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(=\sin30^0\cdot\cos x+\cos30^0\cdot\sin x+\cos30^0\cdot\cos x-\sin30^0\cdot\sin x\)

\(=\dfrac{1}{2}\cos x+\dfrac{\sqrt{3}}{2}\sin x+\dfrac{\sqrt{3}}{2}\cos x-\dfrac{1}{2}\sin x\)

 

HQ
Hà Quang Minh
Giáo viên
25 tháng 9 2023

Ta có:

\(\begin{array}{l}\cos {30^o} = \sin \left( {{{90}^o} - {{30}^o}} \right) = \sin {60^o} = \frac{{\sqrt 3 }}{2};\\\sin {150^o} = \sin \left( {{{180}^o} - {{150}^o}} \right) = \sin {30^o} = \frac{1}{2};\\\tan {135^o} =  - \tan \left( {{{180}^o} - {{135}^o}} \right) =  - \tan {45^o} =  - 1\end{array}\)

\( \Rightarrow E = 2.\frac{{\sqrt 3 }}{2} + \frac{1}{2} - 1 = \sqrt 3  - \frac{1}{2}.\)

18 tháng 8 2021

a) sin 40 - cos 50 =0

b) sin230 + sin240 + sin250 + sin260 = 2

c) cos210 - cos220 + cos230 - cos240 - cos250 - cos270 + cos280 = - sin230

18 tháng 8 2021

\(a.sin40^o-cos50^o=sin40^o-sin40^o=0\)
\(b.sin^230^o+sin^240^o+sin^250^o+sin^260^o=\left(sin^230^0+sin^260^o\right)+\left(sin^240^0+sin^250^o\right)=\left(sin^230^0+cos^230^o\right)+\left(sin^240+cos^240^o\right)=1+1=2\)
\(c.\left(cos^210^o+cos^280^o\right)-\left(cos^220^o+cos^270^0\right)-\left(cos^240^o-cos^250^o\right)+cos^230^o=\left(cos^210^o+sin^210^o\right)-\left(cos^220^o+sin^220^o\right)-\left(cos^240^o+sin^240^0\right)+cos^230^0=1-1-1+\dfrac{3}{4}=-\dfrac{1}{4}\)

15 tháng 12 2018

Chọn A.

Ta có: 7500 = 2.3600 + 300; 4200 = 3600 + 600; -3300 = -3600 + 300; -3900 = -3600 - 300

Nên từ giả thiết ta suy ra:

14 tháng 4 2019

1.

\(\frac{\pi}{2}< x< \pi\\ \Rightarrow cosx< 0,sinx>0,cotx< 0\)

\(cotx=\frac{1}{tanx}=\frac{-1}{3}\)

\(1+tan^2x=\frac{1}{cos^2x}\\ \Rightarrow cosx=\sqrt{\frac{1}{1+tan^2}}=\sqrt{\frac{1}{1+9}}=-\frac{\sqrt{10}}{10}\)

\(sinx=\sqrt{1-cos^2x}=\sqrt{1-\frac{10}{100}}=\frac{3\sqrt{10}}{10}\)

21 tháng 9 2023

a) \(A=2sin30^o+3cos45^o-sin60^0\)

\(\Leftrightarrow A=2.\dfrac{1}{2}+3.\dfrac{\sqrt[]{2}}{2}-\dfrac{\sqrt[]{3}}{2}\)

\(\Leftrightarrow A=1+\dfrac{3\sqrt[]{2}}{2}-\dfrac{\sqrt[]{3}}{2}\)

\(\Leftrightarrow A=1+\dfrac{\sqrt[]{3}\left(\sqrt[]{6}-1\right)}{2}\)

b) \(B=3cos30^o+3sin45^o-cos45^o\)

\(\Leftrightarrow B=3\dfrac{\sqrt[]{3}}{2}+3\dfrac{\sqrt[]{2}}{2}-\dfrac{\sqrt[]{2}}{2}\)

\(\Leftrightarrow B=\dfrac{3\sqrt[]{3}}{2}+\dfrac{2\sqrt[]{2}}{2}\)

\(\Leftrightarrow B=\dfrac{3\sqrt[]{3}}{2}+\sqrt[]{2}\)

30 tháng 4 2019

Chọn C.

Ta có:

14 tháng 10 2021

\(B=\dfrac{1-4\sin^2x\cdot\cos^2x}{\sin^2x+2\sin x\cdot\cos x+\cos^2}+2\sin x\cdot\cos x\\ B=\dfrac{1-4\sin^2x\cdot\cos^2x}{2\sin x\cdot\cos x}+2\sin x\cdot\cos x\\ B=\dfrac{1-4\sin^2x\cdot\cos^2x+4\sin^2x\cdot\cos^2x}{2\sin x\cdot\cos x}=\dfrac{1}{2\sin x\cdot\cos x}\)